A 'great way to get on'? The early career destinations of science, technology, engineering and mathematics graduates. Issue 2 (15th March 2017) - Smith, Emma; White, Patrick
Abstract: Concerns about a shortage of highly skilled workers in the science, technology, engineering and mathematics (STEM) sector have been expressed frequently since the late 1940s. Although these claims have been challenged as being insufficiently grounded in evidence, they have formed the basis of policies directing considerable resources to STEM education, particularly in the university sector. This paper uses data from the Higher Education Statistical Agency from 1994 to 2010, covering more than three million UK graduates, to contribute to the existing research into the purported skills gap in the STEM sector. It examines their destinations six months after graduation to establish the proportion of graduates from different subject areas that enter graduate careers, with a particular focus on STEM graduates and highly skilled STEM occupations. The findings show that only a minority of graduates enter 'graduate' positions within six months of finishing their degree and many find themselves unemployed or underemployed. Overall, STEM graduates fare little better than non-STEM graduates and while graduates in some STEM subjects fare slightly better than average, those with other STEM degrees fare worse than those with non-STEM degrees. The findings appear incompatible with a true shortage of potential STEM workers and raise questions about employers' expectations and the continued subsidisation of STEM degrees.